Moodle course design best practices : design and develop outstanding Moodle learning experiences - Nash, Susan Smith, 1958- (Packt Publishing, 2018)
Fast-paced guide for designing effective Moodle courses; experiment with Moodle's features for free using MoodleCloud Key Features Apply principles of instructional design to create great Moodle learning experiences Enhance collaboration and spur creativity with Moodle Bring together instructional materials, social interaction, and student management functions in your courses Book Description Moodle is a leading virtual learning environment for your online course. This book incorporates the principles of instructional design, showing you how to apply them to your Moodle courses. With this guidance, you will develop and deploy better courses, content, and assessments than ever. This book will guide you as you learn how to build and incorporate many different types of course materials and dynamic activities. You will learn how to improve the structure and presentation of resources, activities, and assessments. All this will help you to create better for self-led courses, instructor-led courses, and courses for collaborative groups. The use of multimedia features to enhance your Moodle courses is also explained in this book. Our goal is to encourage creativity, and the free MoodleCloud hosting option is an ideal place for teachers, students, trainers, and administrators to jump in and play with all the new features, which include powerful new plug-ins, new resources, and activities. Moodle can be your sandbox as well as your castle of learning! With this book, you will build learning experiences that will last your learners' lifetimes. What you will learn Build a course structure that fits your goals Design a unique appearance Manage the resources and activities Tips for better organization of your course content Select and set up assessments Include effective instructional strategies Incorporate competency frameworks Run and archive webinars Motivate learners by incorporating badges Explore MoodleCloud Who this book is for If you create courses with Moodle, this book is for you. It can be used by teachers, instructors, training managers, Moodle administrators, instructional technologists, instructional designers, and e-learning entrepreneurs. Prior experience with Moodle will be helpful.